Rekrutmen Calon Karyawan Tetap - M. Setiadi Hartoko (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2016)
Recruitment of prospective employees remain in Indonesia should be in accordance with Law No. 13 Year 2003 on Employment. Through the law, the companies or institutions are required to follow the recruitment process in accordance listed. Therefore, the authors conducted research on campus LP3I whether the proc ess undertaken adequate or not and to know what obstacles faced by institutions related to the recruitment of permanent employees. Expected compliance with government laws, related to the recruitment has been indeed and unhindered so that these institutions have always considered following government regulations and the Republic of Indonesia.